Sosialisasi tentang Pentingnya Peran Orang Tua bagi Remaja dan Anak-Anak dalam Penggunaan Internet - Wijana, Miki; Setiawan, Rizal (Ma'soem University, 2022)
The development of information and communication technology is a very rapid breakthrough. Internet is a medium of information and communication that is connected globally and can be accessed by anyone and anywhere. Cibungur village is one of the villages in the Rancakalong sub-district, Sumedang district. People are very worried about the negative impact of the development of internet technology, especially for children and adolescents. With the phenomenon of technological development in Cibungur Village, it is necessary to provide understanding regarding the involvement of parents, especially those with small children or teenagers, how to anticipate children's dependence on accessing the internet. This research uses that method Community Based Research (CBR), including building the basic principles and concepts of research, research planning, Information gathering and analysis then action on the findings. After the implementation of the training, the Cibungur Village community represented by village officials, community leaders and parents with young children/adolescents could better understand the important role of parents for children in using the internet. So that children can control their daily activities, do not abandon the habit of studying through stationery, avoid addiction or bad habits of excessive use of electronic devices and use the internet as needed.